2010
DOI: 10.1055/s-0029-1245657
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Fußbodendesinfektion auf die mikrobielle und partikuläre Belastung der Raumluft in Augen-OP-Räumen mit Verdrängungslüftungsbereichen

Abstract: It appears that frequent cleaning disinfection of floors is not necessary if a laminar air flow ventilation system is installed. Under these conditions, targeted disinfection of visibly soiled surfaces appears to be sufficient. Generally, the duration of surgical procedures should be kept as short as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…5) ). Floor disinfection had no impact on particle and germ counts in the operating field when laminar air flow was employed [ 5 ], whereas surface disinfection under mixed airflow conditions in combination with aseptic covering of furniture and equipment resulted in an approx. 10 fold reduction of particle and microbial contamination in the operating area.…”
Section: Discussionmentioning
confidence: 99%
“…5) ). Floor disinfection had no impact on particle and germ counts in the operating field when laminar air flow was employed [ 5 ], whereas surface disinfection under mixed airflow conditions in combination with aseptic covering of furniture and equipment resulted in an approx. 10 fold reduction of particle and microbial contamination in the operating area.…”
Section: Discussionmentioning
confidence: 99%
“…However, the RK Ia indubitably compares favorably with any mixed ventilation system (room class Ib), i.e., physically, a significantly higher reduction rate of germ and particles loads (OR field, tables of instruments) has been proven [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ], [ 28 ], [ 29 ], [ 30 ], [ 31 ], [ 32 ], [ 33 ], [ 34 ]. Therefore, from the perspective of prevention, an RK Ia OR is generally recommended for all operations that have the highest requirements for very low germ rates (e.g., implantation of large endoprotheses in the fields of orthopedics/trauma surgery).…”
Section: Recommendations For User Unitsmentioning
confidence: 99%
“…Pollutants emitted within this protected area are discharged directly into the back of the room by a directional flow. The entry of pollutants emitted outside of this protected area is blocked to such a degree that it not even necessary to disinfect the floor in between ophthalmological operations [ 29 ]. In this concept, a supply air flow that is virtually free of germs and particles diminishes (by diluting and discharging the air) all pollutants emitted inside the room at a high dilution speed.…”
Section: Recommendations For User Unitsmentioning
confidence: 99%
“…Concomitantly, it was demonstrated that particle counts in an ophthalmologic operating theatre with laminar flow did not increase although routine floor disinfection between procedures was stopped [15]. Refraining from routine surface disinfection, however, shortened turnaround times.…”
Section: Air As a Source Of Microbial Transmissionmentioning
confidence: 99%